A Kinetic Map of the Homomeric Voltage-Gated Potassium Channel (Kv) Family - Ranjan, Rajnish; Logette, Emmanuelle; Marani, Michela; Herzog, Mirjia; Tâche, Valérie; Scantamburlo, Enrico; Buchillier, Valérie; Markram, Henry (Frontiers in Cellular Neuroscience, 2019)
The voltage-gated potassium (Kv) channels, encoded by 40 genes, repolarize all electrically excitable cells, including plant, cardiac and neuronal cells. Although these genes were fully sequenced decades ago, a comprehensive kinetic characterization of all Kv channels is still missing, especially near physiological temperature. Here, we present a standardized kinetic map of the 40 homomeric Kv channels systematically characterized at 15°C, 25°C and 35°C. Importantly, the Kv kinetics at 35°C differ significantly from commonly reported kinetics, usually performed at room temperature. We observed voltage-dependent Q10 for all active Kv channels and inherent heterogeneity in kinetics for some of them. Kinetic properties are consistent across different host cell lines and conserved across mouse, rat and human. All electrophysiology data from all Kv channels are made available through public website (Channelpedia). This dataset provides a solid foundation for exploring kinetics of heteromeric channels, roles of auxiliary subunits, kinetic modulation, and for building accurate Kv models.